A STUDY ON CARBON ISOTOPE OF CO2 AND CH4 IN WESTERN DIENG PLATEU BY GAS CHROMATOGRAPHY- ISOTOPE RATIO MASS SPECTROMETER (GC-IRMS) - Hanik Humaida (Indonesian Journal of Chemistry, 2005)
The carbon isotope can be used to evaluate volcanism phenomenon of volcano. The study of carbon isotope of CO2 and CH4 was carried out in western Dieng Plateau by mass-spectrometer. Before analysis, sampel was separated by gas chromatography using a Porapak-Q column and a FID (Flame Ionization Detector) detector. The gas was oxidized by copper oxide at 850oC before being ionized in mass-spectrometer for isotope analysis. The CO2 content in Candradimuka crater (-4.10 O/OO), indicated that the gas may be as volcanic gas. The other CO2 from Sumber and western Gua Jimat, had isotope value  of -10.05 and -12.07 O/OO, respectively, indicating contamination from crustal and subduction material. The carbon isotope of CH4 gas from Pancasan village was -63.42 O/OO, that may be categorized as biogenic gas.